2012
DOI: 10.1038/ismej.2012.57
|View full text |Cite
|
Sign up to set email alerts
|

One millimetre makes the difference: high-resolution analysis of methane-oxidizing bacteria and their specific activity at the oxic–anoxic interface in a flooded paddy soil

Abstract: Aerobic methane-oxidizing bacteria (MOB) use a restricted substrate range, yet >30 species-equivalent operational taxonomical units (OTUs) are found in one paddy soil. How these OTUs physically share their microhabitat is unknown. Here we highly resolved the vertical distribution of MOB and their activity. Using microcosms and cryosectioning, we sub-sampled the top 3-mm of a water-saturated soil at near in situ conditions in 100-μm steps. We assessed the community structure and activity using the partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
94
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(108 citation statements)
references
References 96 publications
11
94
3
Order By: Relevance
“…Our experiments show that Methylosarcina species are clearly the most responsive without addition of urea. This is in contrast with the niche differentiation observed at high spatial resolution in rice soil microcosms (Reim et al, 2012). The presence of Methylosarcina-related MOB in the surface layer of thin-layer microcosms and not in the methane-oxygen interface implies that Methylosarcina thrives under low-methane ("oligotrophic") conditions, in contrast to Methylobacter, which dominates the zone of high-methane flux.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Our experiments show that Methylosarcina species are clearly the most responsive without addition of urea. This is in contrast with the niche differentiation observed at high spatial resolution in rice soil microcosms (Reim et al, 2012). The presence of Methylosarcina-related MOB in the surface layer of thin-layer microcosms and not in the methane-oxygen interface implies that Methylosarcina thrives under low-methane ("oligotrophic") conditions, in contrast to Methylobacter, which dominates the zone of high-methane flux.…”
Section: Discussioncontrasting
confidence: 60%
“…A similar result was observed in SIP analyses of lake sediment microcosms using a metagenomic approach . Hence, we speculate that the observations by Reim et al (2012) may also be explained by weak competitive abilities of Methylosarcina instead of being restricted to low-methane habitats. A comparison of 16S rRNA gene and pmoA gene sequences revealed that Methylobacter was detected in a higher proportion in the MOB-16S rRNA gene phylogenetic tree than in the pmoA gene phylogenetic tree.…”
Section: Discussionmentioning
confidence: 80%
“…Hence, a large ammonium load may be a strong selecting force for the methanotrophic community composition in these reactors. On the contrary, type II methanotrophs are thought to be present mainly as resting cells in other environments (26,33), which is also indicated by the qPCR analysis in this study (Fig. 2).…”
supporting
confidence: 68%
“…The pmoA gene is present in virtually all methanotrophs, allowing a wider coverage of the methanotroph inventory than mmoX (a gene encoding the soluble form of MMO), which is confined to only some methanotrophs. Methylocella-like mmoX sequences have been retrieved from diverse environments (25), but their ecological relevance at circumneutral pH remains uncertain (26). Hence, we focused on the pmoA gene diversity of the potentially active community after 12 days of in vitro incubation.…”
mentioning
confidence: 99%
“…It seems that type II methanotrophs are dominant in bulk soil whereas both type I and II methanotrophs exist in rhizosphere and surface soils (13,(24)(25)(26)(27)(28). Two separate studies of pmoA transcripts recently indicated that type I rather than type II methanotrophs were particularly active in the rhizosphere (29) and surface soils (30). The activity of methanotrophs (transcription of pmoA) in bulk soil has never been analyzed before, although bulk soil is the largest reservoir of methanotrophs in the rice field (31) and may become a habitat suitable for aerobic methanotrophs upon drainage (32).…”
mentioning
confidence: 99%